Strength and Weakness of Oxford English Textbook “Aim High 5” by Susan Iannuzzi and Paul Kelly Based on the 2013 Curriculum - Rofiq Noorman Haryadi; Doni Anggoro Ari Santoso; Pahrizan Pahrizan; Dodi Ilham; Denok Sunarsi (Universitas Cokroaminoto Palopo, 2021)
This descriptive qualitative research aimed to know the strength and weakness of Oxford English Textbook “Aim High 5” By Susan Iannuzzi and Paul Kelly Based on the 2013 Curriculum. The data sources are the 2013 Curriculum, syllabus, scientific approach, Aim High 5. The resources are analyzed, examined, and explored. The results show that the scientific approach method, one of the teaching methods in the 2013 Curriculum, is found in every unit of the reading text. Moreover, the reading texts are presented in systematic way, it can be seen from all the sections in reading texts. There are 4 subtopic steps or activities in reading sections: 1). Before reading, 2). Read, 3). Understanding ideas, and 4). Vocabulary. It seems that the authors prepare the textbook well, which can be seen from the connectivity of the material, extended exercise, interesting story in every reading text. On the contrary, the weakness of “Aim High 5” Based on the 2013 Curriculum including the steps of reading sections, which are a bit monotone. It can be seen that all units, from unit 1 to 10 has the same steps such as before reading, read, understanding ideas, vocabulary. Moreover, many of vocabularies are unfamiliar, that rarely heard by some of the students especially the students who live in countryside or village, and the students who do not have access to internet and library. Likewise, structure or sentences are sometime little bit difficult to understand by them. It is because the English is the foreigner language in Indonesia, so the knowledge of the English is limited according to some area in Indonesia.